With regard to respect: a framework for governance of educational virtual communities. (15th November 2004) - Bell, Frances; Heinze, Aleksej
We use theories of computer-mediated communication and virtual communities to explore the governance of web-based educational communities. Two parallel cycles of action research are reported to inform our discussion, one intervention driven by perceived needs within the department, and the other that occurred as an ad hoc response to a student request. Our analysis recognises that governance arrangements for web-based educational communities in general, and discussion fora one such group in particular, have to operate within a web of existing and evolving institutional policies and procedures. We propose a framework for the development of norms for educational discussion forums in an institutional setting.